PENGARUH FENOMENA PHONE-SNUBING (PHUBBING) TERHADAP CIVIC DISPOCITION MAHASISWA PPKN UNIVERSITAS LAMPUNG - Yunida Nurlina; Ana Mentari; Nurhayati Nurhayati; Mohammad Mona Adha; Fitra Endi Fernanda (STKIP Subang, 2026)
The present study aimed to examine the effect of the phone-snubbing (phubbing) phenomenon on the civic disposition of students in the Civic Education (PPKn) Study Program at the University of Lampung. This research employed a descriptive method with a quantitative approach. The subjects of the study were PPKn students from the 2022, 2023, and 2024 cohorts, with a total sample of 75 respondents. Data were collected using primary techniques, namely questionnaires, and supported by interviews. Data analysis was performed using SPSS version 25. The findings revealed a significant negative effect of phubbing on students’ civic disposition, as indicated by a simple linear regression test with a significance value of 0.000 (p < 0.05) and a coefficient of determination (R²) of 0.312, showing that phubbing contributed 31.2% to the variation in civic disposition. The regression coefficient of -0.640 suggested that higher phubbing intensity corresponded to lower civic disposition. This relationship may be influenced by indicators such as communication disturbance and phone obsession, which were shown to adversely affect the quality of social interactions and various aspects of civic disposition, including academic responsibility, self-discipline, social awareness, politeness, and the ability to listen and compromise. These results highlight the importance of addressing phubbing behaviors to foster civic character development among university students. Keywords: phubbing, civic disposition, students, civic character